Traditional hill agroforestry systems in Garhwal Himalaya - Kumar, Munesh; Singh, Chatar (Indian Journal of Agroforestry, 2020)
The Garhwal Himalaya is rich in multipurpose tree species (MPTs) which are traditionally grown in agricultural fields, preferred by farmers and managed in agroforestry for basic needs. In present paper a list of 23 MPTs is presented with their brief notes on their flowering, fruiting, distribution, uses and their abundance in agroforestry. Among the five agro forestry sites, each site was dominated by Grewia oppositifolia, which is the most important and common multipurpose tree of this and entire region of Garwhal Himalaya. Besides, other important preferred tree species in agroforestry systems are Celtis australis, Bauhinia spp., Ficus spp., Terminalia spp etc. The forests of sub-tropical region of Garhwal Himalaya are shrinking at much faster rate due to high population pressure, urbanization and human activities, and most of the hills become denuded. The shrinking forests covers also reduced the numbers of livestock population from the area and resultant farmyard manure based agro ecosystems. Therefore, promoting and maintenance of traditional agroforestry tree species could be helpful to rehabilitate the situations of the region by enhancing the production of fodder, firewood and small timber for the villagers as well as the productivity of the agriculture on sustained basis.